Innovative Design for Energy Storage Cold Chain Logistics Vehicles - L. C. Shih; Y. J. Chiu; J. S. Huang (International Transactions on Electrical Energy Systems)
To meet the demand for cold chain logistics through green transportation, this study designed a solar-powered vehicle with energy storage ability for cold chain logistics operations. The designed vehicle has solar panels on its roof that power the refrigeration system of the vehicle during transportation. This use of solar energy enables the fuel and energy consumption of the vehicle to be reduced. Moreover, the energy storage ability of the designed vehicle enables its refrigeration system to continue running continuously even when the vehicle is switched off. The designed vehicle reduces carbon and CO2 emissions by at least 36.3%, thereby mitigating urban air pollution. This study develops a business model to help relevant companies reduce carbon credit costs, ensure compliance with regulations and standards, and enhance corporate image. Thus, the designed vehicle contributes to the achievement of the sustainable development goals (SDGs) of the United Nations and the global objective of realizing net-zero carbon emissions by 2050; particularly, SDG 9 relates to the industry, innovation, and infrastructure; SDG 12 relates to responsible production and consumption; and SDG 13 relates to climate action.